Evidence of early cortical atrophy in MS: relevance to white matter changes and disability. - De Stefano, N; Matthews, P; Filippi, M; Agosta, F; De Luca, M; Bartolozzi, M; Guidi, L; Ghezzi, A; Montanari, E; Cifelli, A; Federico, A; Smith, S (2003)
OBJECTIVE: To assess cortical gray matter (GM) changes in MS and establish their relevance to clinical disability and to inflammatory changes of white matter (WM) in patients with the relapsing-remitting (RR) and primary progressive (PP) forms of the disease. METHODS: Conventional MRI examinations were obtained in patients with definite MS who had either the RR or the PP form of the disease. An automated analysis tool was used with conventional T1-weighted MR images to obtain total and cortical brain volumes normalized for head size. Total brain lesion load was estimated on conventional proton density and T2-weighted MR images. The relationship between volumetric MR measures and scores of clinical disability was assessed. RESULTS: Normalized cortical volumes (NCV) were lower for both RR and PP MS patients than for normal control subjects (p < 0.001) but were similar between the two patient groups (p > 0.5). NCV decreases in both patients groups were detected even in those patients with short disease duration (<5 years; p < 0.001 in RR MS and p < 0.05 in PP MS) and minimal brain lesion volume (<5 mL; p < 0.0001 in RR MS and p < 0.005 in PP MS). Measures of NCV in individual patients were negatively correlated with T2-weighted lesion volume (r = -0.47, p < 0.001) and disease duration (r = -0.25, p < 0.05) only in the patients with RR MS. NCV correlated with Expanded Disability Status Scale scores across all of the patients, but the strength of the correlation was stronger (p < 0.05) for PP (r = -0.64, p < 0.0001) than for RR (r = -0.27, p = 0.04) MS patients. CONCLUSIONS: These data confirm substantial neocortical volume loss in MS patients and suggest that neocortical GM pathology may occur early in the course of the disease in both RR and PP MS patients and contribute significantly to neurologic impairment. Although a proportion of this neocortical pathology may be secondary to WM inflammation, the extent of the changes suggests that, especially in patients with PP MS, an independent neurodegenerative process also is active.